Menghidupi Iman dalam Budaya: Model Praksis dalam Konteks Masyarakat Dayak Kalimantan Tengah - Elsa Oktavia; Revalina Revalina; Lelo Lelo; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study is motivated by the importance of understanding theology not merely as a theoretical concept, but as a reflection of faith that is lived within the cultural context of society. In the context of the Dayak community in Central Kalimantan, there is a close relationship between cultural values and spiritual life, thus requiring a theological approach that can bridge the two. This study aims to analyze the praxis model in contextual theology and its application in the life of the Dayak community. The method used is a descriptive qualitative approach through literature study by examining various relevant sources. The results show that the praxis model emphasizes the relationship between lived experience, faith reflection, and concrete action. Cultural values such as togetherness and mutual cooperation are in line with Christian teachings; however, there are also traditional practices that create tension with faith. The church plays an important role in addressing this through a dialogical and reflective approach. The implications of this study indicate that the application of the praxis model enables believers to live out their faith in a contextual, relevant, and transformative way in daily life without losing their cultural identity.Top of Form